Identification of ESBL-producing and blaSHV gene Harboring Enterobacter spp. Isolated from Bloodstream Infections of Hospitalized Patients During 10 Years in South of Iran (Shiraz) - Sedegheh Nematolahi; Ahmad Mosadegh; Jalal Mardaneh; Bahman Poorabbas (Iranian South Medical Journal, 2016)
Background: Multidrug resistance is emerging among gram negative bacteria that cause hospital infections or community acquired around the world. The aims of this study were (1) determination of antibiotic susceptibility profile of Enterobacter spp. isolates recovered from blood, (2) phenotypic identification of ESBL and AmpC-producing isolates, (3) identify MDR strains, and (4) identification isolates harboring blaSHV gene using PCR method.